Design of the high voltage isolation transmission module with low delay for ECRH system on J-TEXT - 马海燕;夏冬辉;王之江;崔芳泰;余振雄;金易坤;刘昌海 (Plasma science & technology, 2018)
As a flexible auxiliary heating method,the electron cyclotron resonance heating（ECRH） has been widely used in many tokamaks and also will be applied for the J-TEXT tokamak.To meet requirements of protection and fault analysis for the ECRH system on J-TEXT,signals of gyrotrons such as the cathode voltage and current,the anode voltage and current,etc should be transmitted to the control and data acquisition system.Considering the high voltage environment of gyrotrons,isolation transmission module based on FPGA and optical fiber communication has been designed and tested.The test results indicate that the designed module has strong anti-noise ability,low error rate and high transmission speed.The delay of the module is no more than 5 μs which can fulfill the requirements.